Politeness Strategies in Barbershop - Wardoyo, Anom Haryanto Hari; Mahmud, Murni; Nur, Sahril (Har Press Indonesia, 2023)
This article is related to the politeness strategies used in the Barbershop. This research was conducted to determine politeness strategies used by the barber and their reasons for using those strategies. This research is descriptive qualitative research. To get the data, some field observations. In conducting the analysis, the step used is to identify politeness strategy, classify and explain politeness strategies based on Brown's theory and Levinson (1987). The results showed that there were four strategies found, namely bald on record, politeness in the positive and the negative and off record. The most dominant strategy is positive politeness strategy. The positive politeness strategy is actually a positive-oriented strategy the listener's positive face, the positive self-image he claims for himself. This strategy is mostly affected where the conversation takes place. Another finding from this research is the most dominant strategy in positive politeness used in conversation. In fact, the conversation is basic positive-politeness techniques used to minimize and to avoid confrontation and deep evaluation reasons also to make people talk differently. Because of this conversation, it makes the atmosphere better and fun, and so can the customer manage the relationship and not threaten the face of the heir.